Why has the share of training firms declined in Switzerland? - Juerg Schweri; Barbara Mueller (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2007)
The Swiss mass apprenticeship system is market based. The share of training firms as a percentage of all firms is therefore an indicator which receives much public attention. The share of training firms declined markedly from 1985 to 2001, dropping from 24.7 to 17.6%. This has often been interpreted as a sign of firms' decreasing willingness to train apprentices. We use data from the firm census to assess whether the decline in the share of training firms can instead be explained by a range of independent variables. Besides firm characteristics and regional variables, we include supply-side factors such as demographic developments in the relevant age cohorts, which have been ignored in the empirical literature so far. Using pooled probit models, fixed-effects models and a Blinder-Oaxaca type decomposition, we are able to explain the variation in the share of training firms over time to a large extent. The main reasons for the decrease are increasing numbers of very small firms, shifts in industry composition, a reduction in the number of young people and an increasing share of young people going to grammar school. We discuss these developments in turn and conclude that they do not, in our opinion, provide sufficient reasons for state interventions in the apprenticeship market.
Keywords: 330; Ausbildungsverhalten - Determinanten; Ausbildungsbetrieb - Quote; betriebliche Berufsausbildung - Entwicklung; Betrieb; Betriebsgröße; Kleinstunternehmen; Wirtschaftsstrukturwandel; demografischer Wandel; Jugendliche; Ausbildungsentscheidung; Bildungsökonomie; Schweiz